In vitro Mechanistic Exploration of Novel Spiropyrrolidine Heterocyclic Hybrids as Anticancer Agents - Kumar, Raju Suresh; Almansour, Abdulrahman I.; Arumugam, Natarajan; Mohammad, Faruq; Kumar, Raju Ranjith (Frontiers in Chemistry, 2020)
Novel spiro acenaphthylene pyrrolo[1,2-b]isoquinoline/pyrrolidine hybrids have been achieved through Pictet-Spengler/Eschweiler-Clarke reactions depending on the substitution in the benzyl ring. The in vitro biological efficacy of N-methyl spiropyrrolidine derivatives toward different cancer and non-cancer cell lines revealed that these novel spiro heterocyclic hybrids induced cancer cell death at moderate concentrations, while slight reduction in non-cancer cell viability at the higher concentrations. The analysis of cancer cells proved that the major pathway of cell death is apoptosis and in addition, the role of caspases is confirmed by the appearance of fluorescent cells in microscopic images. Therefore, this study indicates a sustainable way of treating cancer cells by inducing apoptotic pathways and associated caspases, while simultaneously protecting the non-cancer cells.